Genetic analysis of dual-purpose sweetpotato genotypes using simple sequence repeat markers and phenotypic traits. Issue 1 (2nd January 2022) - Shumbusha, Damien; Shimelis, Hussein; Laing, Mark; Mashilo, Jacob
ABSTRACT: The new generation sweetpotato [ Ipomoea batatas L. (Lam.)] varieties are valued as dual-purpose types for food and fodder in the crop-livestock mixed-farming systems in sub-Saharan Africa. The objective of this study was to determine the genetic diversity present among dual-purpose sweetpotato genotypes using simple sequence repeat (SSR) markers and phenotypic traits to identify complementary genotypes for direct production and breeding. Twenty-four sweetpotato genotypes were genotyped using nine selected and highly polymorphic SSR markers and dual-purpose phenotypic traits. The genotypes were field-evaluated using a randomized complete block design with three replications in two representative locations in Rwanda. Genotypes differed significantly ( p < 0.05) for dual-purpose traits and other assessed phenotypic traits. Genotype "Ukerewe" had the highest fresh root yield (18.24 t ha −1 ), followed by genotype '8–1038ʹ (17.63 t ha −1 ). The top-performing genotypes for fresh vine yield were "Wagabolige" (23 t ha −1 ) and 'NASPOT13ʹ (21.64 t ha −1 ). The mean expected heterozygosity value was 0.69, indicating adequate genetic variation in the tested germplasm. Cluster analysis grouped the genotypes into three distinct groups, which aided in the identification of genotypes with high fodder and storage root yields, which were SPK004 and K5132/61 from Group I; 4–160, Ukerewe and RW11-2910 from Group II; and RW11-1860, Wagabolige and 2005–179 from Group III. The identified genotypes should be useful genetic resources for production and development of high-performing dual-purpose sweetpotato cultivars in Rwanda.